(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2025)
Federico Garcia Lorca was a Spanish poet and playwright linked to the socalled Generation of 27, who was assassinated at the beginning of the Civil War in 1936, at a very young age. Even so, his work was prolific and widely acknowledged as one of the most important poets of the Spanish language. In this article we approach his children’s poetry through its graceful charm and the sonority implicit in it, as well as three poems to which I wrote music.